Microbial inoculants and Trichoderma viride consortia for growth promotion and disease management in ginger: Microbial consortia for growth and disease management in ginger - Haritha, T R; Gopal, K S (Journal of Spices and Aromatic Crops, 2021)
A study was conducted to evaluate the effect of microbial inoculants consortia on ginger under field conditions. Three biofertilizers comprising of Azospirillum lipoferum (nitrogen fixer KAU-AZO), Bacillus megaterium (phosphate solubilizer KAU-PSB), Bacillus sporothermodurans (potash solubilizer KAU-KSB) and two biocontrol agents namely, Pseudomonas fluorescen (KAU-PF) and Trichoderma viride (KAU-TV) were used in the study. Compatibility studies revealed that all the isolates were compatible with each other. However, P. fluorescens and T. viride were incompatible with each other under in vitro. Under field evaluation, consortia of microbial inoculants performed better than the single inoculants in terms of yield and disease management. The organic Adhoc package recorded the minimum incidence of rhizome rot (2.09 %) among all the treatments. However, KAU-AZO + KAU-PSB + KAU-KSB + KAU-TV recorded the minimum rhizome rot (5.23%) incidence among the consortia. In the case of Rhizoctonia leaf blight disease, consortia of KAU-AZO + KAU-PSB + KAU-KSB + KAU-PF showed the minimum incidence (5.21%). In general, consortium of A. lipoferum, B. megaterium (PSB), B. sporothermodurans (KSB) and T. viride was the most efficient for plant growth promotion and disease management in ginger.